COVID-19 aus Sicht der Infektiologie - Khatamzas, Elham; Rothe, Camilla; Kroidl, Inge (DMW - Deutsche Medizinische Wochenschrift, 2020)
The control and management of infection with the novel SARS-CoV-2 virus requires multidisciplinary work between specialists on all levels. This article aims to provide an overview of the current knowledge of COVID-19 from the view of infectious diseases physicians including all the uncertainties of our understanding of the pathogenesis and immunity.
Keywords: COVID-19; Infektiologie; Behandlung; SARS-CoV-2-Serologie